FEKTIVITAS KEGIATAN ONE WEEK ONE JUZ PADA PENINGKATKAN KESEHATAN MENTAL MASYARAKAT DALAM MENGHADAPI WABAH COVID 19 - ., Muslimah; Wijaya, Rafi Bagus Adi (Universitas Sahid Surakarta, 2021)
This study aims to determine the effectiveness of one week one juz to improve people's mental health in the face of the Covid-19 outbreak. Participants in this study consisted of 10 people who were members of the WhatsApp khataman Al-quran one week one juz group. Participants' age range was 20-25 years and had mental health scores in the moderate to low category. The research design used was the one-group pretest-posttest design. The data collection of this study used a modified MHI-38 scale. The method of analysis used the paired sample t test technique to test the difference in gains score on the pre test and post test results. The results of the paired t test show the value of sig = 000> 0.05 which indicates that there is an effect of one week one juz activity on mental health. The results of the Gain test score got a score of 2.82 which indicates that there is a high level of effectiveness between one week one juz activities on mental health.